A Novel Erythromycin Resistance Plasmid from Bacillus Sp. Strain HS24, Isolated from the Marine Sponge Haliclona Simulans - Barbosa, Teresa M. (Public Library of Science, 2014)

(untitled) (PLoS One)
A better understanding of the origin and natural reservoirs of resistance determinants is fundamental to efficiently tackle antibiotic resistance. This paper reports the identification of a novel 5.8 kb erythromycin resistance plasmid, from Bacillus sp. HS24 isolated from the marine sponge Haliclona simulans. pBHS24B has a mosaic structure and carries the erythromycin resistance gene erm(T). This is the first report of an erythromycin resistance plasmid from a sponge associated bacteria and of the Erm(T) determinant in the genus Bacillus.